2021
DOI: 10.1177/0276236620960634
|View full text |Cite
|
Sign up to set email alerts
|

Animals in Dreams of Children, Adolescents, and Adults: The UK Library Study

Abstract: Animal dreams have fascinated mankind for ages. Empirical research indicated that children dream more often about animals than adults and dogs, cats, and horses are the most frequent animals that appear within dreams. Moreover, most dreamer-animal interactions are negative. The present study included 4849 participants (6 to 90 yrs. old) reporting 2716 most recent dreams. Overall, 18.30% of these dreams included animals with children reporting more animal dreams that adolescents and adults. The most frequent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
(41 reference statements)
2
6
0
Order By: Relevance
“…A recent study explored more than two thousands dreams ( [17]). It found that the most frequent animals in animal dreams were dogs, cats, and horses.…”
Section: Animal Dreamsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study explored more than two thousands dreams ( [17]). It found that the most frequent animals in animal dreams were dogs, cats, and horses.…”
Section: Animal Dreamsmentioning
confidence: 99%
“…One limitation of the study was the sex of participants, because most of participants were female. According to Schredl et al ( [17]), the sex of participants may affect potential kinds of animals in dreams. For example ( [17], p.10), "dogs and horses were more often found in female dreams whereas fantasy/prehistoric animals were more prominent in male dreams."…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most dreamer-animal interactions (Yo Adhirohati) in dreams (Swapne) are negative (Skandato Bhayam). 48 Animals (Mayura, Kukkuta, Basta & Mesha) in dreams (Swapne) generally represents wakinglife experiences of a dreamer with those animals. 49 It has been found that dreams with animal figures (Mayura, Kukkuta, Basta & Mesha) have a great deal of violent activity and the dreamer experiences fear (Skandato Bhayam).…”
Section: Animals In Dreamsmentioning
confidence: 99%
“…Moreover, the frequency and species of animals in dreams differed among various groups. Many studies showed that children dreamed more about animals than adults (Avila-White et al, 1999; Schredl & Blagrove, 2021; Strauch & Lederbogen, 1999), and the occurrence of the animal dreams varied from males to females (Domhoff, 1999; King & DeCicco, 2007). Other studies showed that the male and female dreams of animals in 6% and 4%, respectively, with significant differences (Domhoff, 1999); dreams about animals occurred in 7%, and individuals with more pain dreamed more about animals (King & DeCicco, 2007).…”
mentioning
confidence: 99%